Rhinocricidae Systematics I: The taxonomic placement of the species of Zipyge Chamberlin, 1925 and Oxypygides Chamberlin, 1922 (Diplopoda: Spirobolida: Rhinocricidae: Oxypyginae) - Bond, Jason E.; Marek, Paul E. (Zootaxa, 2003)
The rhinocricid genera Zipyge and Oxypygides are considered to be junior synonyms of the genus Oxypyge.The following new combinations are established:Oxypyge lapidicina (Chamberlin, 1922) and Oxypyge mesites (Chamberlin, 1922), both from Oxypygides. The current status of rhinocricid generic level taxonomy is introduced, the limits of Oxypyge Silvestri are discussed, and the type specimens of the type species of the nominal genera Zipyge and Oxypygides are redescribed.